2019
DOI: 10.3390/mi10070460
|View full text |Cite
|
Sign up to set email alerts
|

A Resonant Pressure Sensor Based upon Electrostatically Comb Driven and Piezoresistively Sensed Lateral Resonators

Abstract: This study proposes a microfabricated resonant pressure sensor in which a pair of double-ended tuning forks were utilized as resonators where comb electrodes and single-crystal silicon-based piezoresistors were used for electrostatic excitation and piezoresistive detection, respectively. In operations, pressures under measurements deform the pressure-sensitive diaphragm to cause stress variations of two resonators distributed on the central and side positions of the pressure-sensitive diaphragm, where the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In comparison to previous resonant pressure micro sensors based on electrostatic excitation and capacitive detection (e.g., Xie [7], Sun [8]), the sensors developed in this study were featured with lower crosstalk and thus higher SNRs. In comparison to the counterparts based on electrostatic excitation and piezoresistive detection (e.g., Shi [13], Shi [17]), the sensor developed in this study demonstrated higher SNRs, higher differential sensitivities, wider working temperature ranges and lower device dimensions due to structure optimization. In addition, the DETF resonators can operate in the anti-phase mode, which ensures that the proposed sensors demonstrate higher pressure cycling performances (e.g., shift, hysteresis and repeatability error) than what was reported in [8].…”
Section: Experimental Characterizationsmentioning
confidence: 96%
See 2 more Smart Citations
“…In comparison to previous resonant pressure micro sensors based on electrostatic excitation and capacitive detection (e.g., Xie [7], Sun [8]), the sensors developed in this study were featured with lower crosstalk and thus higher SNRs. In comparison to the counterparts based on electrostatic excitation and piezoresistive detection (e.g., Shi [13], Shi [17]), the sensor developed in this study demonstrated higher SNRs, higher differential sensitivities, wider working temperature ranges and lower device dimensions due to structure optimization. In addition, the DETF resonators can operate in the anti-phase mode, which ensures that the proposed sensors demonstrate higher pressure cycling performances (e.g., shift, hysteresis and repeatability error) than what was reported in [8].…”
Section: Experimental Characterizationsmentioning
confidence: 96%
“…In order to compare the SNRs of the proposed sensor with previously reported counterparts, the outputs of three types of resonant pressure sensors in responses to excitation signals from 50 to 150 kHz with bias voltages of 20 V were measured under atmospheric pressure (~ 100 kPa) and room temperature (~ 22 °C). As shown in Figure 5c, the developed sensor demonstrates a high SNR of 67.64 dB compared with 54.00 dB (Shi’s sensor [17]) and 38.33 dB (Xie’s sensor [7]). Note that, the sensors based on electrostatic excitation/piezoresistive detection shows lower noise levels due to the negligible crosstalk between the detection electrode and driving electrode compared with the sensor based on electrostatic excitation/capacitance detection.…”
Section: Experimental Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) proto-type view of resonator with a dimension of 7 Ö 7 mm2. (d) resonant sensor mounted on top of a covar-header [142]. Kuo et al [143]integrated a multiple sensor on a single innovative System-on-chip design resonator structure.…”
Section: Etchingmentioning
confidence: 99%
“…DRUCK 16 proposed a novel structure that eliminates adjacent output signals, such as the first mode output; however, numerous beams are used, and thus the resulting structure is complex. Shi et al 17 proposed another beam combination structure by setting the piezoresistive detection beam at the end of the resonant beam, and the beam combination structures have good shielding ability for adjacent modes, but the resonator quality factor was only~10,000 with vacuum packaging. Welham et al 15 proposed the use of two straight beams as coupling and detection beams for shielding the adjacent mode, and the increase in the stiffness owing to the coupling beam decreases the sensitivity.…”
Section: Introductionmentioning
confidence: 99%